2003
DOI: 10.1002/adma.200304687
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Nickel Sulfide Submicrometer Hollow Spheres

Abstract: does not require an activation energy but it is certainly characterized by dissipation associated with the viscosity at the boundary between the crystalline domains and the amorphous matrix. A detailed description of this process goes well beyond the scope of this introductory communication.The recording speed of the holograms in our samples is of the order of tens of seconds, much slower than in the photorefractive composites with the smallest response times, [18,19] and this represents the main limit of our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(67 citation statements)
references
References 17 publications
0
67
0
Order By: Relevance
“…[178,179] After the silica shell is formed by the hydrolysis and condensation of TEOS, the liquid PDMS cores can be easily removed by solvent extraction. [180] In addition to sol-gel processes, many other synthetic approaches, such as hydrothermal methods [158] and g-irradiation, [181][182][183][184] have been employed in combination with emulsion templating to synthesize hollow particles of various crystalline materials, including metals, [185,186] oxides [187] and sulfides, [157,188,189] and inorganic/polymer composites. [183,184] Bao et al synthesized Ni hollow spheres (300-450 nm) using NiSO 4 and NaH 2 PO 2 as precursor and reducing agent respectively.…”
Section: Emulsion Dropletsmentioning
confidence: 99%
“…[178,179] After the silica shell is formed by the hydrolysis and condensation of TEOS, the liquid PDMS cores can be easily removed by solvent extraction. [180] In addition to sol-gel processes, many other synthetic approaches, such as hydrothermal methods [158] and g-irradiation, [181][182][183][184] have been employed in combination with emulsion templating to synthesize hollow particles of various crystalline materials, including metals, [185,186] oxides [187] and sulfides, [157,188,189] and inorganic/polymer composites. [183,184] Bao et al synthesized Ni hollow spheres (300-450 nm) using NiSO 4 and NaH 2 PO 2 as precursor and reducing agent respectively.…”
Section: Emulsion Dropletsmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29][30][31][32] There are, however, relatively few reports on the deposition of thin films of nickel and palladium chalcogenides. Films of nickel sulfide [33][34][35][36] have been deposited via solution growth techniques, and nickel [37][38] and palladium sulfide [37,39] have been deposited by both CVD, and non-CVD techniques. [40] Cheon et al [37] have reported deposition of stoichiometric NiS and PdS from both thermal and photochemical CVD routes using M(S 2 COCHMe 2 ) 2 , (M = Ni or Pd), and Nomura and Hayata studied the deposition of NiS 1.03 from Ni(S 2 CNEt 2 ) 2 on Si(111) substrates at 350-400°C by low-pressure metal-organic (LP-MO) CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, despite the success in the preparation of NiS hollow structures, the synthesis of hollow structures of NiS by a simple route still remains as a significant challenge. [15,43,44] Herein, we provide a facile strategy to prepare hollow a-NiS and b-NiS spheres via the Kirkendall effect under different hydrothermal conditions. Unlike template-directed approaches, this route avoids complicated and tedious operational procedures for the removal of the templates.…”
Section: Introductionmentioning
confidence: 99%